Medical Students` perception Regarding Using Study Guides in Clinical Education - Shakiba Sadat Tabatabaee; Fatemeh Keshmiri (Pizhūhish dar Āmūzish-i ̒ulūm-i Pizishkī)
Introduction: Study guide is a tool that helps to direct learners on the education path as a road map and can facilitate their learning process. Moreover, it provides useful information for educators to achieve optimal learning outcomes. Therefore, the present study aimed to investigate the students' perception regarding the application of study guides in clerkship and internship courses in the clinical education process at Shahid Sadoughi University of Medical Sciences. Methods: This analytical-cross-sectional study was conducted at Shahid Sadoughi University of Medical Sciences in 2020-2021. In this study, the viewpoints of 62 students regarding the use of study guides in the process of clinical education were investigated through a validated Agarwal's (2017) questionnaire. The content validity ratio (CVR) in all items was higher than 0.49, and the content validity index (CVI) in all items was reported to be higher than 0.79, with no items being omitted from the questionnaire. The required data were collected using the field research method. Data were analyzed using descriptive (mean, standard deviation, and percentage) and inferential tests (Students T-Test) in SPSS software (version 16.0). Results: The mean age of participants in this study was 25.32±0.71 years, and 33 participants (53.2%) were female. The mean satisfaction scores of the students from the internship and clerkship courses were calculated as 3.55±0.97 and 3.44±1.59, respectively, indicating the acceptable satisfaction of the externs and interns with the study guide. The results showed that there was no significant difference in the views of the participants regarding the application of the study guide in internship and clerkship courses (P=0.45). The highest mean score was reported in the "instructiveness" item (4.14±0.69). Conclusion: The results showed that the students considered the study guide an informative tool and a motivator for creating motivation for learning through increasing awareness and knowledge concerning the educational program and the learning process. Systematic planning is recommended for the use of learning guides to manage students' learning in medical school.